A rare case of incidental mucinous adenocarcinoma with osseous metaplasia associated with cysts of the presacral space - Lorusso, Dionigi; Santis, Stefania De; Lantone, Giulio; Armentano, Raffaele (Turkish Journal of Gastroenterology, 2019)
Abstract Cite this article as: Lorusso D, De Santis S, Lantone G, Armentano R. A rare case of incidental mucinous adenocarcinoma with osseous metaplasia associated with cysts of the presacral space. Turk J Gastroenterol 2019; 30(5): 495-6.